Pelatihan Beauty Class Sebagai Upaya Mendorong Beautypreneur Pada Remaja Perempuan Gen-Z di Kota Gorontalo. - Yayu Isyana Pongoliu (Lembaga Pengembangan Kinerja Dosen, 2022)
Gen-Z is a generation that is highly influenced by the importance of appearance regarding beauty and fashion. The beauty and personal care business in Indonesia is estimated to reach 154 T with a growth rate of 4.3% per year. This is a big business opportunity, especially for Gen Z, which is predicted to become a demographic bonus in the next few years. This beauty class training aims to train young women's life skills by taking advantage of opportunities from the beauty sector and Gen-Z consumption behavior to become something of economic value or beautypreneur. The methods used in this training activity are lectures, discussions and practice. The result of this training activity is that participants have knowledge about the beauty business prospects which can be a source of income for them and have mastered basic make-up techniques.